Account of the diversity of tunneling spectra at the germanene/Al(1 1 1) interface. (1st November 2019) - Sciacca, Davide; Peric, Nemanja; Berthe, Maxime; Biadala, Louis; Pirri, Carmelo; Derivaz, Mickael; Massara, Natalia; Diener, Pascale; Grandidier, Bruno
Abstract: Despite the wealth of tunneling spectroscopic studies performed on silicene and germanene, the observation of a well-defined Dirac cone in these materials remains elusive. Here, we study germanene grown on Al(1 1 1) at submonolayer coverages with low temperature scanning tunneling spectroscopy. We show that the tunnelling spectra of the Al(1 1 1) surface and the germanene nanosheets are identical. They exhibit a clear metallic behaviour at the beginning of the experiments, that highlights the strong electronic coupling between the adlayer and the substrate. Over the course of the experiments, the spectra deviate from this initial behaviour, although consecutive spectra measured on the Al(1 1 1) surface and germanene nanosheets are still similar. This spectral diversity is explained by modifications of the tip apex, that arise from the erratic manipulation of the germanium adlayer. The origin of the characteristic features such as a wide band gap, coherence-like peaks or zero-bias anomalies are tentatively discussed in light of the physical properties of Ge and AlGe alloy clusters, that are likely to adsorb at the tip apex.